Peran Kompensasi dan Kepuasaan Kerja terhadap Pengaruh Stress Kerja - Ratri Wisnu Pertiwi; Syamsul Hadi; Aulia Rosiana (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
Purpose - This research was conducted with the aim of knowing the role of compensation and job satisfaction in mediating the effect of job stress. Research method - This study uses regression analysis one method to determine the causal relationship between variables with other variables. The sample that meets the feasibility analysis is 60 respondents consisting of private institutions in Yogyakarta. Findings - From the regression test proves that compensation has a significant effect on work stress as well as job satisfaction has a significant effect on work stress. Given that job satisfaction plays an important role so that employees can provide optimal work results so that organizational goals can be achieved. Keywords: compensation, job satisfaction, job stress